Antioxidant properties and L-asparaginase activities of endophytic fungi from Cymbidium orchids - Chua, Ru Wei; Song, Keang Peng; Ting, Adeline Su Yien (Folia microbiologica, 2024)
This study profiled the various endophytic fungi isolated from the orchid Cymbidium sp. and their L-asparaginase production and antioxidant potential. The L-asparaginase production was first screened through qualitative plate screening then quantified by the Nesslerization method. The antioxidant potential was quantified via the 2,2-diphenyl-1-picrylhydrazyl assay. A total of 30 endophytic fungi were isolated and all fungal isolates exhibited various degrees of radical scavenging activities (45.28% to 76.4%). Isolate Lasiodiplodia theobromae (C11) had the highest antioxidant capacity, represented by the lowest IC50 value (5.75 mg/mL) and highest ascorbic acid equivalent antioxidant capacity value (12.17 mg/g). Additionally, 16 isolates produced L-asparaginase (53.33%), which includes primarily species of Fusarium proliferatum, Fusarium fujikuroi, Fusarium incarnatum, and Fusarium oxysporum. A new isolate has also been discovered from Cymbidium orchid, Buergenerula spartinae (C28), which showed the highest L-asparaginase activity (1.736 unit/mL). These findings supported the postulation that medicinal species of Orchidaceae such as Cymbidium sp. harbor endophytes that are producers of L-asparaginase and antioxidants with various potential applications.
Keywords: Antioxidants; endofyty; Phylogeny; Fusarium; Fungi; antioxidancia; houby; fylogeneze; Asparaginase; asparaginasa; Orchidaceae; Endophytes